A step closer towards achieving universal health coverage: the role of gender in enrolment in health insurance in India - Ziegler-Wirtz, Susanne; Srivastava, Swati; Parmar, Divya; Basu, Sharmishtha; Jain, Nishant; De Allegri, Manuela (BMC health services research, 2024)
There is limited understanding of how universal health coverage (UHC) schemes such as publicly-funded health insurance (PFHI) benefit women as compared to men. Many of these schemes are gender-neutral in design but given the existing gender inequalities in many societies, their benefits may not be similar for women and men. We contribute to the evidence by conducting a gender analysis of the enrolment of individuals and households in India’s national PFHI scheme, Rashtriya Swasthya Bima Yojana (RSBY).